An Analysis of Students’ Vlogs toward Majapahit Heritage Sites in Speaking Class: Pride and Improvement - Sherly Citra Putri; Fatqu Rofiqoh Dewi (Journal of ELT, Linguistics, and Literature, 2025)
This research aimed to describe students’ exploration vlogs toward Majapahit heritage sites in speaking class impacted to their pride and improvement in speaking English. This research needs to be done to prove that students could improve speaking skill by using historical and cultural material from their living area. It is necessary to provide instructions and outdoor activities to get to know the history and culture of the nation in order to make students smoothly introduce it better than other nations’ culture, then they can introduce and promote it globally in internet by uploading vlog. It used qualitative descriptive design whereas data was collected through observation, interview, questionnaire and vlogs from twenty-four students in second year of English Education Department, University of Mayjen Sungkono. The results showed students gained new vocabularies and knowledge from their outdoor activities while they took data in location, interviewed the keepers and local vendors. A significant improvement appeared in their speaking skill since they shared the information about Majapahit heritage globally by using English as international language. Students’ vlog about Majapahit heritage proved to bring back their pride as local and improved their speaking performance